PENGARUH ADVERTISING TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH DENGAN SELEBRITIS ENDORSER SEBAGAI VARIABEL MODERASI - Hema Malina (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
This purpose of this research is to analyze the impact of the advertising and endorser their effects towards decision buying on Wardah cosmetics, where advertising (X1) become independents variables, celebrity endorser (X2) become moderating variable, and buying decision (Y) as a dependent variable. The population of this research is consumers of Wardah cosmetics in Surakarta. Sample that used in this research are 100 respondents. Technique sampling method that used in this research is accidental sampling. While its survey method used questionnaires. Then analyzed method that used in this research includes validity test, reliability test, classical assumption test, multiple linear regressions, t-test, F-test, coefficient determination test and with the result test. According to this research results, regression formula Y = 7,372 + 0,138X1 + 0,379X2. Statistic data analysis, indicators in this research showed that all data were valid and reliable. Hypothesis testing used t-test showed that the advertising and celebrity endorser significantly influences its buying decision. The result test endorser has no significant moderating advertising its buying decision. Keywords: Advertising, celebrity endorsers, buying decisions.